FIRM CHARACTERISTICS AND WORKING CAPITAL MANAGEMENT OF LISTED CONSUMER GOODS COMPANIES IN NIGERIA - Sambo, Jidauna Akila; Saidu, Sani; Shagari, Shamsudden Ladan (Kashere Journal of Management Sciences, 2024)
Working capital management plays an important role in success and failure of firm. The main objective of the study is to examine the impact of firm characteristics on working capital management of listed consumer goods companies in Nigeria. An ex-post facto research design was adopted for the study. The target population is twenty-one (21) consumer goods companies in Nigeria. The study sampled sixteen (16) consumer goods companies for a period of 11 years (2011-2021). Multiple regression technique was employed to analyze the data using STATA 14. The result reveals that block holder ownership, profitability and firm size have significant positive relationship with cash conversion cycle. Accordingly, the study recommends that consumer goods companies and other allied companies should take measures to improve their profitability by growing their revenues and curtailing their expenses so as to generate sufficient internal resources. The study also recommends that consumer goods companies and other related companies should take advantage of their size and manage accordingly their working capital.